Plant Specificity of Necrotrophic Fungi Isolated on Wild Radish (Raphanus raphanistrum L.) in Tunisia - T. Souissi, N. DjÃ©bali, (Journal of Phytology, 2009)
The specificity of several fungal species isolated from the wild radish (Raphanus raphanistrum L.) was evaluated on two Brassicacea species, garden radish (Raphanus sativus L.) and rapeseed (Brassica napus L.) under controlled conditions. Most fungal species have attacked the three Brassicaceae plants, suggesting that wild radish, is a relay host for several diseases in garden radish and rapeseed field crops. However, two isolates belonging to, Cercospora armoraciae and Colletotrichum higginsianum, were pathogenic on wild radish plants but not on the other Brassicaceae species. These preliminary results indicate that these two fungi species may be considered as potential biocontrol agents against this weed in Tunisia. Further studies must be conducted on other plant species in order to determine the spectrum of infection of these two fungal species.